2011
DOI: 10.1111/j.1467-3010.2010.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Red meat in the diet: an update

Abstract: This paper provides an update of a previous review 'Red Meat in the Diet' published in the Nutrition Bulletin in 2005. An update on red meat consumption levels in the UK and other countries is provided, and a summary of the nutritional content of red meat in the diet is given. Current evidence on dietary and lifestyle factors associated with red meat consumption and the effects of red meat intake on health and chronic disease outcomes are discussed. As there is now continued debate about the environmental impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 171 publications
(192 reference statements)
1
114
1
9
Order By: Relevance
“…The meat and milk of ruminant animals also contain TFA, and, with the use of PHVO falling, they have become a more significant source. It has been estimated that approximately 40% to 50% of TFA in the UK diet now comes from ruminant dairy products and meat (Wyness et al, 2011). Considerable debate exists Dietary fatty acids and cardiovascular disease as to whether TFA from such 'natural' sources have the same impact on CVD risk as that from PHVO.…”
Section: Tfa and Cardiovascular Riskmentioning
confidence: 99%
“…The meat and milk of ruminant animals also contain TFA, and, with the use of PHVO falling, they have become a more significant source. It has been estimated that approximately 40% to 50% of TFA in the UK diet now comes from ruminant dairy products and meat (Wyness et al, 2011). Considerable debate exists Dietary fatty acids and cardiovascular disease as to whether TFA from such 'natural' sources have the same impact on CVD risk as that from PHVO.…”
Section: Tfa and Cardiovascular Riskmentioning
confidence: 99%
“…It is important to note that in a study where macronutrient content of test meals was varied while energy density remained constant, no differences in satiety or subsequent energy intake were observed (48) . It may be that energy density of a food or diet may be more important in determining its satiating effect than its protein content (49) .…”
Section: Satiety and Weight Controlmentioning
confidence: 99%
“…In the UK, meat and meat products contribute up to 40 % and 37 % of average daily protein consumed by males and females respectively (2) . However, epidemiological studies have indicated an association between red and processed meat intake and an increased risk of developing cardiovascular disease (3) and certain cancers (4) , and people are being advised to reduce their consumption of these foodstuffs.…”
mentioning
confidence: 99%